The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1590/s0102-09352012000500016
|View full text |Cite
|
Sign up to set email alerts
|

Anticoccidial efficacy of drinking water soluble diclazuril in the control of Eimeria acervulina oocysts on experimentally-infected broiler chickens

Abstract: The experiment was carried out with 150 Cobb broiler chickens divided into 3 groups with 50 birds each. The groups of infected chickens orally received 1ml of inoculum containing 3x10 3 Eimeria acervulina sporulated oocysts at 12 days of age. Group 1 was kept as a positive control with infected non-medicated birds, group 2 was medicated with diclazuril (1%) with a dose of 1mL/4 L of drinking water for 2 successive days, 5 days after infection, while group 3 was kept as negative control with non-infected and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
3
1
0
Order By: Relevance
“…The lowest average body mass was recorded in chickens treated with both anticoccidials (Ro+Herb). Our results of increased weight gain and body weight in broilers treated with both the synthetic and herbal anticoccidials are in line with some previous data and resulted from their beneficial effects [29,31] . Positive effects on production performance resulting from the use of chemical and herbal anticoccidials have already been described [32] .…”
Section: Discussionsupporting
confidence: 92%
“…The lowest average body mass was recorded in chickens treated with both anticoccidials (Ro+Herb). Our results of increased weight gain and body weight in broilers treated with both the synthetic and herbal anticoccidials are in line with some previous data and resulted from their beneficial effects [29,31] . Positive effects on production performance resulting from the use of chemical and herbal anticoccidials have already been described [32] .…”
Section: Discussionsupporting
confidence: 92%
“…This indicated that the broilers immunologically responded to the developmental stages of the parasites at different intensities or time, resulting in varied oocyst output. The observed gradual reduction in oocyst output in the treated and non-treated experimental broilers from primary-secondary -tertiary infections is similar to the report of Assisi et al [18]. These authors reported that this may be due to the stimulation and production of immune bodies (T and B cells) in the non-treated broilers at primary and secondary infections and action of Amprolium in the treated chickens.…”
Section: Discussionsupporting
confidence: 89%
“…The varied prepatent periods associated with the infection, the unsporulated oocyst, sporulated oocyst, schizonts, merozoites and gametocytes which were 0, 120, 264, 96 and 48 h respectively are similar to the reports of Assisi et al [18] who also recorded 120 h prepatent period for birds infected with sporulated oocyst of Eimeria tenella. However the prepatent periods are inconsistent with the other stages of the parasite.…”
Section: Discussionsupporting
confidence: 86%
“…After viewing the symptoms of the infected animals like general weakness, bloody diarrhea and no interest in feeding, stool samples are taken to be tested microscopically using both direct smear and floating ways to examine the ovarian cysts. The infection level is to be determined by Assis et al, 2012 that depends on counting the number of those ovarian cysts in the sample in the slide, then calculating the cysts numbers per 1 gm stool multiplied by 10 and counting them by the microscope [23].…”
Section: Lab Testsmentioning
confidence: 99%